2006
DOI: 10.1139/o05-151
|View full text |Cite
|
Sign up to set email alerts
|

TXM13 human melanoma cells: a novel source for the inhibition kinetics of human tyrosinase and for screening whitening agents

Abstract: Research involving whitening agents requires several steps of experimentation, and the initial step is to test whitening agents with human melanocytes and those with human tyrosinase. Unfortunately, it takes a long time to gather human melanocytes, and these cells have some limitations when it comes to performing experiments, such as their passage difficulties and their cost. In this study, we suggest that the TXM13 human melanoma cells could be a useful cell candidate for studying human tyrosinase inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Tyrosinase, TRP-1, and TRP-2 play important roles in melanin biosynthesis [ 27 ]. Thus, the mechanism underlying the effect of skin whitening agents involves inhibition of melanin production by decreasing tyrosinase activity [ 28 ]. The expression of tyrosinase, TRP-1, and TRP-2 genes is known to be regulated by MITF [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tyrosinase, TRP-1, and TRP-2 play important roles in melanin biosynthesis [ 27 ]. Thus, the mechanism underlying the effect of skin whitening agents involves inhibition of melanin production by decreasing tyrosinase activity [ 28 ]. The expression of tyrosinase, TRP-1, and TRP-2 genes is known to be regulated by MITF [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…We monitored such changes using spectrofluorometry. The inhibitory mechanism of arabinose resembled that of a copper chelator, but differs in that arabinose did not directly bind to copper atoms at the active site [34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Experimentally, our kinetic studies consistently confirmed all results and the model described in Scheme 1. The inhibitory mechanism of PA was partly similar to those of copper chelators but still has different aspect that PA did not directly bind to coppers at the active site [33, 34]. V max value changes were predicted by docking simulation that PA might not compete with L-DOPA for docking because the binding sites are not located in the active site pocket.…”
Section: Discussionmentioning
confidence: 99%